Gold-Hall and Earth-Dragon - Lee, Alvin A. (University of Toronto Press, 1998)
Demonstrates how Beowulf?s symbolic system reveals itself through the metaphorical workings of the Old English words, and how the poem might have been experienced and interpreted by the Anglo-Saxons in the light of other Old English poems.
10.3138/9781442675407